2021
DOI: 10.1021/acsabm.1c00949
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Design and Manufacturing of Bio-scaffolds for Bone Reconstruction

Abstract: Bio-scaffolds are synthetic entities widely employed in bone and soft-tissue regeneration applications. These bio-scaffolds are applied to the defect site to provide support and favor cell attachment and growth, thereby enhancing the regeneration of the defective site. The progressive research in bio-scaffold fabrication has led to identification of biocompatible and mechanically stable materials. The difficulties in obtaining grafts and expenditure incurred in the transplantation procedures have also been ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 296 publications
0
12
0
Order By: Relevance
“…However, a more detailed insight into this topic is provided in dedicated reviews. 20,25,[194][195][196][197][198]…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…However, a more detailed insight into this topic is provided in dedicated reviews. 20,25,[194][195][196][197][198]…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…To enhance the osteogenic potential of scaffolds, silk has been combined with a variety of polymers and other biomaterials such as HAP [ 14 , 98 , 99 ] that has similarity with the structure of mineralized human bone and affinity to hard tissues [ 14 , 98 , 99 , 111 ]. Moreover, the combination between silk fibroin and HAP combines the positive properties of both materials.…”
Section: The Potential Of Silk Fibroin In Bone Tissue Engineeringmentioning
confidence: 99%
“…Recent studies have shown that the printed infill pattern is also important for the biocompatibility of biomimetic scaffolds [ 28 , 29 , 30 ]. Triply periodic minimal surfaces (TPMS) have gained attention due to their high surface-to-volume ratio and interconnected porosity, which closely mimic the structure of natural materials [ 31 ].…”
Section: Introductionmentioning
confidence: 99%